Byron and Latin Culture : Selected Proceedings of the 37th International Byron Society Conference. - Cochran, Peter (Cambridge Scholars Publishing, 2013)
Byron and Latin Culture consists of twenty-three papers, most of which were given at the 37th International Byron Conference at Valladolid, Spain, in July 2011. An introduction by the editor describes in detail the huge influence which the major Latin poets had on Byron: his borrowings, imitations, parodies, and echoes have never been catalogued in such detail, and it becomes clear that many ideas central to Don Juan, in particular, derive from Ovid, Virgil, Petronius, Martial and the other ...